Multilayered Cultures of NSCLC cells grown at the Air-Liquid Interface allow the efficacy testing of inhaled anti-cancer drugs - Volkov, Yuri; Movia, Dania; Volkov, Yuri; Prina-Mello, Adriele (My University, 2018)
Evidence supports the advantages of inhalation over other drug-administration routes in the treatment of lung diseases, including cancer. Although data obtained from animal models and conventional in vitro cultures are informative, testing the efcacy of inhaled chemotherapeutic agents requires humanrelevant preclinical tools. Such tools are currently unavailable. Here, we developed and characterized in vitro models for the efcacy testing of inhaled chemotherapeutic agents against non-small-cell lung cancer (NSCLC). These models recapitulated key elements of both the lung epithelium and the tumour tissue, namely the direct contact with the gas phase and the three-dimensional (3D) architecture. Our in vitro models were formed by growing, for the frst time, human adenocarcinoma (A549) cells as multilayered mono-cultures at the Air-Liquid Interface (ALI). The in vitro models were tested for their response to four benchmarking chemotherapeutics, currently in use in clinics, demonstrating an increased resistance to these drugs as compared to sub-confuent monolayered 2D cell cultures. Chemoresistance was comparable to that detected in 3D hypoxic tumour spheroids. Being cultured in ALI conditions, the multilayered monocultures demonstrated to be compatible with testing drugs administered as a liquid aerosol by a clinical nebulizer, ofering an advantage over 3D tumour spheroids. In conclusion, we demonstrated that our in vitro models provide new human-relevant tools allowing for the efcacy screening of inhaled anti-cancer drugs
PUBLISHED
Keywords: Drug-administration; Anti-cancer drugs; Non-small-cell lung cancer (NSCLC)